2015
DOI: 10.1098/rspb.2014.1517
|View full text |Cite
|
Sign up to set email alerts
|

Assessing introduction risk using species’ rank-abundance distributions

Abstract: Mixed-species assemblages are often unintentionally introduced into new ecosystems. Analysing how assemblage structure varies during transport may provide insights into how introduction risk changes before propagules are released. Characterization of introduction risk is typically based on assessments of colonization pressure (CP, the number of species transported) and total propagule pressure (total PP, the total abundance of propagules released) associated with an invasion vector. Generally, invasion potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Chan et al . () also reported increases in species richness and abundance following ballast water exchange during transoceanic voyages.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Chan et al . () also reported increases in species richness and abundance following ballast water exchange during transoceanic voyages.…”
Section: Discussionmentioning
confidence: 85%
“…; Chan et al . ), and statistical associations (Chan et al . ), have previously demonstrated that increasing voyage durations tend to reduce zooplankton density and richness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gregory 2009; Sylvester et al 2011; Briski et al 2013; Fowler et al 2016). In general, only a fraction of individuals and species survive transport and are introduced to a new location (Lockwood et al 2009; Briski et al 2014; Chan et al 2015a). This is because conditions during the transport process are usually hostile; for instance, physical disturbance and fluctuations in environmental conditions during transport may selectively affect survivorship of entrained organisms (Coutts et al 2010a; Clarke Murray et al 2012; Briski et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This is because conditions during the transport process are usually hostile; for instance, physical disturbance and fluctuations in environmental conditions during transport may selectively affect survivorship of entrained organisms (Coutts et al 2010a; Clarke Murray et al 2012; Briski et al 2014). Therefore, examining the fate of organisms and how assemblage structure varies during transport can provide insights into the introduction potential associated with multispecies vectors (Briski et al 2014; Chan et al 2015a). …”
Section: Introductionmentioning
confidence: 99%